2019
DOI: 10.1016/j.metabol.2019.05.012
|View full text |Cite
|
Sign up to set email alerts
|

A novel nutritional supplement prevents muscle loss and accelerates muscle mass recovery in caloric-restricted mice

Abstract: a b s t r a c tBackground: Muscle atrophy is defined as decreased muscle mass, associated with aging as well as with various chronic diseases and is a fundamental cause of frailty, functional decline and disability. Frailty represents a huge potential public health issue worldwide with high impact on healthcare costs. A major clinical issue is therefore to devise new strategies preventing muscle atrophy. In this study, we tested the efficacy of Vital01, a novel oral nutritional supplement (ONS), on body weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The trends for downregulation of muscle mRNA myostatin levels we report in muscle of malnourished minipigs may play a role in Akt activation since this transforming growth factor is recognized to negatively regulate the activity of Akt [64]. Even if previous studies observed a similar activation of Akt in energy-restricted rodents [22,65], this result should have impacted mTORC1 signaling pathways, and especially 4EBP1 and p70S6K.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 51%
See 1 more Smart Citation
“…The trends for downregulation of muscle mRNA myostatin levels we report in muscle of malnourished minipigs may play a role in Akt activation since this transforming growth factor is recognized to negatively regulate the activity of Akt [64]. Even if previous studies observed a similar activation of Akt in energy-restricted rodents [22,65], this result should have impacted mTORC1 signaling pathways, and especially 4EBP1 and p70S6K.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 51%
“…J o u r n a l P r e -p r o o f 6 During the last decade, several experimental models have been developed, essentially in rodents, to better understand the cellular mechanisms involved in sarcopenia related to malnutrition. Some of these rodent models reproduce the hypermetabolism related to chronic diseases [20,21], others induce a drastic protein-energy restriction to mimic marasmus or kwashiorkor [22,23]. Though, the rodent models present several limitations related to their phylogenetic distance and significant differences compared to humans in terms of eating behavior, circadian rhythm and general anatomy.…”
Section: Introductionmentioning
confidence: 99%
“…Results of the stimulation of PBMCs with memory recall mixes did not suggest any substantial changes in immune function on both groups, although the increased proportion of T and B cells in the novel supplement group may impact the general immune status of the subjects. Of note, the same novel supplement seemed to increase the expression of immune-protective pathways in mice [21]. The study reported in this paper is one of the larger randomized controlled trials with ONS run in community-dwelling participants with (risk of) undernutrition.…”
Section: Discussionmentioning
confidence: 87%
“…Hence, we set out to test a novel whey-based ONS, high in leucine and vitamin D that previously was found to provide additional benefits [19,20] and reinforced with UA that may affect muscle metabolism [17]. This novel ONS was tested in a calorically restricted mouse model and found to preserve muscle mass while affecting regulatory pathways [21]. In this study, we compared the effects of this novel supplement with a standard supplement on body composition, physical functioning, blood markers, and skeletal muscle gene and protein expression in older adults with (or at risk of) undernutrition without changing their activity pattern and without additional exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Loss of muscle mass and associated muscle weakness can be reverted, especially during early stages, through sound exercise and nutritional interventions [19,[63][64][65][66][67][68][69]. Evidence from animal studies shows that nutritional interventions for muscle wasting yield better results when administered early during the development of muscle atrophy [7,70]. erefore, proper screening and management of sarcopenia may support efforts aimed to slow or reverse the progression of physical frailty in old seniors [1].…”
Section: Identification Of Individuals With/or Prone To Sarcopenia (Target Groups)mentioning
confidence: 99%